Acceptance of disease in patients with colorectal cancer - Angelina Kaleta-Pilarska (Śląski Uniwersytet Medyczny w Katowicach, 2022)
Introduction Because of the importance of the problem for public health, which is the knowledge of psychological factors that may affect the course of cancer, a study was carried out to assess the frequency and determinants of disease acceptance in patients with colorectal cancer in the period immediately preceding the surgical intervention. Material and methods 200 patients with colorectal cancer participated in the questionnaire study. In order to identify the final predictors influencing the acceptance of cancer, logistic regression analysis was performed along with the verification of parametrization using the automatic backward selection method. Results Slightly more than half of the respondents (56.5%) with colorectal cancer do not accept their disease in the period immediately preceding the surgical intervention. Among the determinants influencing the acceptance of the disease were the following variables: family history of colorectal cancer and satisfaction with medical care. Conclusions More frequent acceptance of colorectal cancer occurs in patients who declare satisfaction with medical care and among patients with a family history of colorectal cancer.